2021
DOI: 10.1021/acs.langmuir.1c00773
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the Properties of Antibiotics with the Energetics of Partitioning in Colloidal Self-Assemblies and the Effect on the Binding of a Released Drug with a Target Protein

Abstract: The bioavailability of drugs and the monitoring of efficient dosage requires drug delivery through suitable vehicles. The partitioning characteristics of the drugs in the delivery vehicles is determined by their molecular features and structure. A quantitative understanding of the partitioning of drugs into delivery media and its subsequent release and binding to the target protein is essential to deriving guidelines for rational drug design. We have studied the partitioning of aminoglycosides and macrolide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
(108 reference statements)
1
1
0
Order By: Relevance
“…Here also ∼10 nm blue shift was observed as it was observed in the case of micelles of HTAB and TX-100 alone. 32,33 The values of K B and n obtained were (6.03 ± 0.12) × 10 3 M −1 and (1.09 ± 0.06), respectively, which are similar to the values of K B and n obtained in the presence of TX-100 micelles alone. When the ITC experiment was performed, it was found that the isotherm is fitted best to a two sequential site binding model as it was observed in the case of TX-100 alone (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Here also ∼10 nm blue shift was observed as it was observed in the case of micelles of HTAB and TX-100 alone. 32,33 The values of K B and n obtained were (6.03 ± 0.12) × 10 3 M −1 and (1.09 ± 0.06), respectively, which are similar to the values of K B and n obtained in the presence of TX-100 micelles alone. When the ITC experiment was performed, it was found that the isotherm is fitted best to a two sequential site binding model as it was observed in the case of TX-100 alone (Fig.…”
Section: Resultssupporting
confidence: 78%
“…In addition, KAN and NEO do not influence on HSA secondary structure. Using the same technique of CD spectrometry to study the interaction between antibiotics, e.g., kanamycin, and bovine serum albumin (BSA), Judy et al found that due to the stronger affinity toward BSA (relative to HSA), KAN does not modulate the secondary structure of BSA (statistically non-significant) [ 36 ]. Owczarzy et al [ 33 , 37 ] analyzed the interaction between 5-alkyl-12(H)-quino[3,4-b][1,4]benzothiazinium derivatives (Salt1, Salt2) and human carrier proteins, including HSA.…”
Section: Discussionmentioning
confidence: 99%